Fabrication and characterization of graphene quantum dots thin film for reducing cross-sectional heat transfer through smart window - Nguyen, Tam Duy (2021)
Graphene and its derivatives have been reported as materials with excellent electrical and thermal conductivity, allowing for various promising applications. In particular, the large-scale surface coating of graphene-based materials can be employed to minimize cross-sectional heat transfer through the glass window. This study introduces a facile and cost-effective method to fabricate graphene quantum dots (GQDs) thin film on Fluorine-doped Tin Oxide (FTO) glass via casting of the GQDs dispersion and stabilizing with poly-vinyl-pyrrolidone (PVP). The thin film possesses excellent optical properties of GQDs and allows more than 80 % of visible transmittance. The presence of the GQDs thin film shows effective reduction in the cross-sectional thermal diffusivity of FTO glass, from 0.55 mm²/s to zero when measured with laser flash over a 4-second period. This low cost and eco-friendly GQDs thin film will be a promising material for heat management in smart window applications.